Developmental shifts toward structural explanations and interventions for social status disparities - Peretz-Lange, Rebecca; Perry, Jennifer; Muentener, Paul (Cognitive development, 2021)
•At baseline, preschoolers formed personal attributions for novel status disparities.•Verbally framing promoted structural attributions of disparities.•Explanations and interventions both grew more structural over development.•Explanations and interventions for novel status disparities were correlated.•Attributions for status disparities predicted social preferences. As part of their early “essentialist” intuitions, young children view intergroup differences as reflecting groups’ intrinsic natures. In the present study, we explore the nature and development of “structural” reasoning, or view of intergroup differences as reflecting groups’ extrinsic circumstances. We introduced participants (n = 315; ages 5–6, 9–10, and adults) to novel intergroup status disparities that could be attributed to either personal or structural causes. Disparities were verbally framed in either intrinsic, neutral or extrinsic terms. We assessed attributions by asking participants to explain the disparities and to offer interventions for them. We also assessed participants’ status-based social preferences. We found that attributions shifted from personal to structural over development. Explanations and interventions for the disparities were correlated and related to the same predictors (framing and age) and outcomes (social preferences), although interventions were consistently more structural than explanations. Implications for essentialism, causal reasoning, and social development are discussed.